Dynamic behaviour of a full-load cavitation vortex in a Francis turbine draft tube excited at its eigenfrequencies. Issue 1 (June 2021) - Favrel, A; Vagnoni, E; Gomes Pereira, J; Sakamoto, M; Yamaishi, K; Müller, A; Avellan, F; Miyagawa, K
Abstract: The operating range of Francis turbines is limited at full-load conditions by the formation of a cavitation vortex rope that may enter self-oscillations under certain conditions. This induces severe pressure pulsations in the entire system, as well as output power swings putting at risk the integrity of the electro-mechanical components. The understanding of the underlying physical mechanisms and the prediction of the stability of hydropower units at full-load conditions are therefore crucial to ensure a safe extension of their operating range. In the present paper, the dynamic behaviour of a stable cavitation vortex rope at full load is investigated by high-speed visualizations while the test rig is excited at its first and second hydroacoustic eigenfrequencies. It is first demonstrated that the cavitation volume and the pressure in the draft tube are more likely to oscillate at the first eigenfrequency, in agreement with the observations of self-excited oscillations at the first eigenfrequency of the cavitation vortex rope during unstable full-load conditions. In addition, it is observed that the amplitude of both the cavitation volume and pressure fluctuations in the draft tube reach a limit value when the amplitude of the excitation is further increased. Further investigations will determine if this behaviour can be generalized to any full-load conditions and will focus on the determination of the hydro-acoustic parameters of the draft tube cavitation flow based on the behaviour of the vortex rope during forced oscillations.